Geographical Diversity in the Age Specific Anti Müllerian Hormone Levels in Infertile Women: A Hospital Based Cohort Study - Mir Jaffar; Syed Nawaz Ahmad; Monica; Mohammed Ashraf; Sabiha Anjum Shaik; Muhammed Asif (Journal of Human Reproductive Sciences)
Background: Serum anti-Mullerian hormone (AMH) is a significant determinant of ovarian reserve. It is still not clear about the rate at which AMH declines with age and varies across populations. Aim: The present study examined the AMH levels specific to the North and South Indian populations and attempted to establish an age-dependent reference parametrically. Settings and Design: This was a prospective study in a tertiary centre. Materials and Methods: Serum samples were collected apparently from 650 infertile women (327 from North and 323 from South Indians). AMH was measured using an electrochemiluminescent technique. Statistical Analysis Used: Comparison of the AMH data between North and South regions was done by independent t-test. For each age, seven empirical percentiles (3rd, 10th, 25th, 50th, 75th, 90th and 95th) were applied. AMH nomograms for the 3rd, 10th, 25th, 50th, 75th, 85th, 90th and 95th percentiles were produced using the lambda-mu-sigma method. Results: AMH levels remarkably decreased with increasing age in the North Indian population, but in the South Indian population, they did not decline beyond 1.5 ng/mL. Further, in the North Indian population, AMH levels were significantly higher in the age group of 22–30 years (4.4 ng/mL) than in the South Indian population (2.04 ng/mL). Conclusion: The present study suggests a major geographical difference in mean AMH levels according to their age and ethnic background, regardless of their subjacent pathologies.